Spatial Log-Gaussian Cox processes for modeling wildfire ignition risk : the case of the Forest Reserve of Bogotá D.C (2017)
In this paper, we present a methodology for modeling the wildfire ignition risk distribution of the Forest Reserve of Bogotá D.C. We propose to use a spatial point pattern approach for the analysis of the process. From the studied area, we analyzed the spatial pattern of the wildfire occurrence by taking into account the variable importance and the incidence of the four type of covariates on the intensity of the wildfires, such as: anthropic, meteorological, geomorphological and physiognomic. A total of 217 wildfires from 1995 to 2016 were taken into account in the model. The results prove that there is statistical evidence to claim that areas closer to human activities have more occurrence of wildfires.